Intravenous regional anesthesia (IVRA) with forearm tourniquet for short-term hand surgery: A case report - Mendes, Ergun; Cesur, Mehmet; Sen, Elzem; Gocergil, Huseyin (Journal of Surgery and Medicine, 2021)
Intravenous Regional Anesthesia (IVRA) was modified many times since its first use and these changes continue according to the type of surgery. A 36-year-old male patient was operated for trigger finger in the fascia of the first and second carpal bones. Because of the short operation time and for early detection of possible vascular or nerve damage after surgery, the IVRA method was used with the forearm tourniquet containing contrast agent. Forearm tourniquet can be preferred in short-term hand surgeries due to its advantages such as easy application, low side effect profile and early block recovery.